Eating order and childhood obesity among preschoolers in China: A cross-sectional study - Dai, Jin; Yang, Jingyun; Fan, Hailing; Wu, Yixin; Wu, Huilan; Wang, Yun; Tung, Tao-Hsin; Wang, Lizhen; Zhang, Meixian (Frontiers in Pediatrics, 2023)
Background: Early childhood is a critical period for dietary education and development of good eating habits. However, few studies have investigated the effect of eating order in children and childhood obesity in real-world settings. Objective: To examine whether the order in which meats/fish or vegetables are consumed affects the risk of obesity in preschoolers. Methods: We conducted a population-based cross-sectional study using a self-administered online survey on the lifestyle and health behaviors of preschoolers in Taizhou, China. A total of 3,200 parents were invited to take part in the survey, and 2,049 of them completed the questionnaire. Children were classified as having a normal weight, overweight, or obesity using the definitions provided by the International Obesity Task Force, and z-scores for body mass index were calculated. We divided the children's eating order at the beginning of the meal into two groups: “vegetables before meats/fish” or “meats/fish before vegetables”. We analyzed the relationship between what was consumed first at a meal and the overweight status of each child. Results: No difference in body mass index was observed between the children eating meats/fish-first and the children eating vegetables-first during a meal. Children with parents who were affected by obesity were more likely to eat vegetables first. Among children of mothers with obesity, body mass index was significantly higher in the meats/fish-first group than that in the vegetable-first group (2.891 vs. 0.845, P = 0.007). In children whose mothers were affected by obesity, those that ate meats/fish first had a 12.21 times higher risk of being overweight compared with those that ate vegetables first (95% CI:1.22–121.74, P = 0.033). Conclusion: Our findings suggest eating vegetables or meats/fish at the start of a meal does not affect weight status in preschoolers.